The short-term efficacy and safety of induction chemotherapy combined with PD-1 inhibitor or anti-EGFR in locoregionally advanced nasopharyngeal carcinoma - Xiang, Xiaoyong; Chen, Peng; Lan, Fengming; Ma, Li; Jin, Jing; Zhang, Ye (Frontiers in Oncology, 2023)
Purpose This study aimed to investigate the short-term efficacy and safety of induction chemotherapy (IC) combined with PD-1 inhibitor or anti-EGFR in the treatment of locoregionally advanced nasopharyngeal carcinoma (LA-NPC). Methods and materials We retrospectively reviewed the clinical data of 206 patients with LA-NPC, including IC combined with anti-PD-1 (57 patients), IC combined with anti-EGFR (28 patients), and IC alone (121 patients). The short-term efficacy was assessed at the end of IC and one month after overall treatment. According to the RECIST v1.1, the short-term efficacy of cervical lymph nodes and primary nasopharynx foci was divided into complete remission (CR), partial remission (PR), stable disease (SD), and progressive disease (PD). The overall response (ORR) was defined as the sum of CR and PR. Acute toxicities were graded according to the CTCAE v5.0. One-way analysis of variance (ANOVA) was used to compare differences in the numerical variables among groups. Fisher Freeman-Halton test or Pearson Chi-square test was used to compare classified variables. Results The ORR rates of primary nasopharynx foci in IC, anti-EGFR, and anti-PD-1 group were 68.60%, 67.9%, and 94.7%, respectively, and the corresponding rates of ORR in cervical lymph nodes were 78.5%, 71.4%, and 93.0%, respectively. There was a statistical difference in the ORR between the three groups. Further analysis showed that after IC or overall treatment, the CR rate of primary nasopharynx foci in the anti-PD-1 group was significantly higher than the other two groups. The most common adverse effects were hematotoxicity, gastrointestinal toxicity, and transaminase elevation. However, there were no statistical differences in the frequency of any common adverse effects between the three groups. Conclusions The addition of anti-PD-1 based on IC significantly improved the short-term efficacy of LA-NPC and toxicities were tolerable.